Direct ultrasound methods: a confirmatory technique for proper endotracheal intubation in the emergency department. (February 2015) - Abbasi, Saeed; Farsi, Davood; Zare, Mohammad A.; Hajimohammadi, Majid; Rezai, Mahdi; Hafezimoghadam, Peyman
Abstract : Background and objective: Early confirmation of incorrect endotracheal tube (ETT) placement is of vital importance when performing emergency airway management. No ideal confirmation technique has been proposed under all circumstances. Recently, ultrasonography was suggested as a useful tool for confirmation of correct positioning of the ETT. The aim of this study is to assess the diagnostic accuracy of ultrasonography for detection of proper ETT placement. Materials and methods: This prospective study was carried out in the emergency department from February to October 2012. The ultrasonography was performed by a trained senior resident in two phases: (a) as the intubation was being performed (dynamic phase) and (b) after the intubation had been completed (static phase). A linear probe was placed transversely over the cricothyroid membrane during the intubation process (dynamic phase) and on the anterior neck just superior to the suprasternal notch in the static method. Operating characteristics were calculated for both dynamic and static determination of ETT placement. Results: Sixty patients were enrolled in each study group. The sensitivity, specificity, positive predictive value, and negative predictive value of the dynamic technique for determining correct endotracheal intubation were 98.1% [95% confidence interval (CI), 88.8–99.9%], 100% (95% CI, 51.6–100%), 100% (95% CI, 91.5–100%), and 85.7% (95% CI, 42–99.2%), respectively. Using the static technique, all testing characteristics listed previously were 100%. Conclusion: In this study, we found acceptable sensitivity, specificity, positive predictive value, and negative predictive value for prediction of tracheal ETT placement with the use of dynamic and static ultrasonography.